Analisis Penerapan Peraturan Presiden Nomor 75 Tahun 2015 Tentang Rencana Aksi Nasional Hak Asasi Manusia Dalam Kebijakan Hukum Pemerintah Daerah Provinsi Sumatera Utara - Edo Maranata Tambunan; Faisal Akbar Nasution; Mirza Nasution; Jelly Leviza (USU LAW JOURNAL, 2019)
Abstract. The demand for awareness of the protection, respect, enforcement, fulfillment and promotion of human rights is the commitment and responsibility of the state. This form of ethical awareness is manifested and normalized in the form of Presidential Regulation Number 75 of 2015 concerning the National Action Plan for Human Rights as an elaboration of the Vienna Declaration and Program of Action June 25, 1993. This study uses a normative juridical method that is descriptive analytical. While the National Action Plan on Human Rights of the province of North Sumatera is regulated and recommended based on the Minister of Home Affairs Circular Letter No. 180/1319/SJ, which was previously regulated and must be determined based on Presidential Instruction; On the other than funding for the application of National Action Plan for Human Rights in the Regional Government of the province of North Sumatera in the 2015-2019 period is still experiencing budget limitations. So it needs to be recommended to increase the commitment of both central and regional governments by forming legal policies on a human rights perspective and improving and reinforcing the position and governance of the Presidential Instruction as well as the Minister of Circular Letter which is used as a reference or implementing regulation policy rather than Presidential Regulation Number 75 of 2015 concerning National Action Plan on Human Rights as a reference and reporting procedure for regional human rights actions that have been established. Then, the implementation of National Action Plan on Human Rights in the Regional Government of the province of North Sumatera needs to be addressed with a synergy of more rational and adequate budget coverage, as well as establishing harmonious relations between the province of North Sumatera Government's Human Rights Action Team, especially between the Regional Head and the Regional Representative Council in encouraging understanding for protection and the promotion of human rights through a comprehensive and accountable regional budgeting process.   Keywords : human rights, national action plan on human rights, legislation.